DISTRIBUSI Solen sp DI PERAIRAN KABUPATEN BANGKALAN - Eva Ari Wahyuni; I Insafitri; Gatot Ciptadi; Mohammad Nur Ihsan (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2016)
DISTRIBUTION OF Solen sp IN BANGKALAN WATERSSolen sp potential needs to be developed on the island of Madura, particularly in Bangkalan. Solen sp utilization has increased which has the potential to overfishing. Therefore, this study aims to determine the density of Solen sp and their ecology in the waters Modung village, Modung District, Bangkalan. The experiment was conducted in April 2015 using the descriptive method. The materials used include Solen sp and physico-chemical parameters of the environment (temperature, salinity, pH, and substrate). The analyzes were conducted at the Laboratory of Marine Science, Department of Marine Sciences, Trunojoyo University of Madura by using the tool grabsampler, sieveshaker, and pipetting with gravimetric method. The analysis shows the range of values of temperature between 29-300C, salinity between 31-32 ppt, pH were 7.9-8.0 and the type of substrate in the form of sandy mud, as well as the density of Solen sp from 8-10 individuals/m2. All measurement results indicate normal conditions and in accordance with the sea water quality standard for marine life, which can be a suitable habitat for the growth and development of Solen sp. This condition is thought to affect the density of Solen sp.Keywords: Bangkalan, density, distribution, Solen sp, substrate.ABSTRAKPotensi Solen sp perlu dikembangkan di pulau Madura, khususnya di Kabupaten Bangkalan. Pemanfaatan Solen sp mengalami peningkatan sehingga berpotensi overfishing. Untuk itu, penelitian ini bertujuan untuk mengetahui kepadatan Solen sp dan ekologinya di perairan desa Modung, Kecamatan Modung, Kabupaten Bangkalan. Penelitian dilaksanakan pada bulan April 2015 dengan metode deskriptif. Materi dan bahan yang digunakan diantaranya Solen sp dan parameter fisika-kimia lingkungan (suhu, salinitas, pH, dan substrat). Analisa dilakukan di Laboratorium Ilmu Kelautan, Program studi/Jurusan Ilmu Kelautan Universitas Trunojoyo Madura dengan menggunakan alat grabsampler, sieveshaker, dan pemipetan dengan metode gravimetri. Hasil analisa menunjukkan kisaran nilai suhu 29-300C, salinitas 31-32 ppt, pH 7.9-8.0, dan jenis substrat berupa lumpur berpasir, serta kepadatan Solen sp 8-10 individu/m2. Semua hasil pengukuran menunjukkan kondisi normal dan sesuai dengan baku mutu air laut untuk biota laut, sehingga dapat menjadi habitat yang cocok untuk tumbuh dan kembang Solen sp. Kondisi ini diduga mempengaruhi kepadatan Solen sp. Kata kunci: Bangkalan, distribusi, kepadatan, Solen sp, substrat.